Assessment of postoperative pain management practices in Cameroon, Ivory Coast and Senegal: A multi-national survey. (July 2021) - Kane, Oumar; Boua, Narcisse; Hentchoya, Romuald; Seck, Modou; Fall, Amy N; Barry, Mamadou S
Inadequately controlled postoperative pain impacts patients' functional recovery and may affect the quality of life after surgery. Our multinational, cross-sectional study conducted online between November 2017 and January 2018 surveyed anaesthetists' conformity with established postoperative pain control guidelines and looked at pain assessment, dissemination of information to patients, staff training and creation and use of treatment protocols. Of the 170 respondents, only six applied postoperative pain management recommendations. The proportion of respondents who reported regular staff training; the regular provision of pre-operative information to patients; the existence and use of written protocols; and the number conducting at least one pain assessment a day was not just suboptimal, but embarrassingly low.